2015
DOI: 10.1111/crj.12346
|View full text |Cite
|
Sign up to set email alerts
|

Mortality prediction to hospitalized patients with influenza pneumonia: PO2/FiO2 combined lymphocyte count is the answer

Abstract: Introduction Community‐acquired pneumonia (CAP) severity scores perform well in predicting mortality of CAP patients, but their applicability in influenza pneumonia is powerless. Objectives The aim of our research was to test the efficiency of PO2/FiO2 and CAP severity scores in predicting mortality and intensive care unit (ICU) admission with influenza pneumonia patients. Methods We reviewed all patients with positive influenza virus RNA detection in Beijing Chao‐Yang Hospital during the 2009–2014 influenza s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 35 publications
8
65
1
Order By: Relevance
“…To further explore whether corticosteroid therapy at a certain dose range is effective for a certain group of influenza pneumonia patients or not, we performed stratified analysis of patients with different disease severity, based on PaO 2 /FiO 2 on admission. This stratification is of great importance, because PaO 2 /FiO 2 is a key factor predicting mortality and may respond to corticosteroid use . In the present study, based on the largest dataset to date, we found that corticosteroids have a tendency to reduce mortality of patients with severe influenza A(H1N1)pdm09 viral pneumonia who have PaO 2 /FiO 2 <300 mm Hg.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…To further explore whether corticosteroid therapy at a certain dose range is effective for a certain group of influenza pneumonia patients or not, we performed stratified analysis of patients with different disease severity, based on PaO 2 /FiO 2 on admission. This stratification is of great importance, because PaO 2 /FiO 2 is a key factor predicting mortality and may respond to corticosteroid use . In the present study, based on the largest dataset to date, we found that corticosteroids have a tendency to reduce mortality of patients with severe influenza A(H1N1)pdm09 viral pneumonia who have PaO 2 /FiO 2 <300 mm Hg.…”
Section: Discussionmentioning
confidence: 48%
“…This stratification is of great importance, because PaO 2 /FiO 2 is a key factor predicting mortality and may respond to corticosteroid use. 30,37 In the present study, based on the largest dataset to date, we found that corticosteroids have a tendency to reduce mortality of patients with severe influenza A(H1N1) Despite being an important factor related to the efficacy of corticosteroids, dosage was mentioned in few studies published to date. 17,21 In the current study, we further performed stratified analysis based on the doses of corticosteroids and found that only lowto-moderate dose of corticosteroids could lower the mortality rate in severe influenza A(H1N1)pdm09 viral pneumonia patients with PaO 2 / FiO 2 <300 mm Hg.…”
Section: Discussionmentioning
confidence: 59%
“…During the H1N1 influenza A pandemic in 2009, a large proportion of severe cases were young patients who experienced acute respiratory failure [25,26]. Another issue to consider is that the current severity tool that relies on PSI and CURB-65 scores was possibly derived from patients diagnosed primarily with bacterial and atypical bacterial pneumonia rather than influenza pneumonia [20,27]. In fact, Guo et al reported that CURB-65 scores were not powerful predictors of mortality in the context of viral pneumonia [28].…”
Section: Discussionmentioning
confidence: 99%
“…3 Influenza may represent a novel host risk factor for this invasive fungal infection. Meanwhile, the mortality rate among co-infected patients has been found to be approximately 50%-60%, 4 which is approximately 5 times that of hospitalized patients with influenza alone.…”
Section: Introductionmentioning
confidence: 99%